2011
DOI: 10.1074/jbc.m109.089607
|View full text |Cite
|
Sign up to set email alerts
|

ATP Modulates Interaction of Syntaxin-1A with Sulfonylurea Receptor 1 to Regulate Pancreatic β-Cell KATP Channels

Abstract: ATP-sensitive potassium (K ATP ) channels are regulated by a variety of cytosolic factors (adenine nucleotides, Mg2؉ , phospholipids, and pH). We previously reported that K ATP channels are also regulated by endogenous membrane-bound SNARE protein syntaxin-1A (Syn-1A), which binds both nucleotide-binding folds of sulfonylurea receptor (SUR)1 and 2A, causing inhibition of K ATP channel activity in pancreatic islet ␤-cells and cardiac myocytes, respectively. In this study, we show that ATP dose-dependently inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…MLCK (myosin light chain kinase) phosphorylates myosin IIA (event 8), which induces its relocalization and association with the actin ring surrounding granules [important for maintenance of the fusion pore in an open conformation and for providing energy for discharge of granule contents (event 9) as well as cortical actin remodeling (event 10)] to allow insulin granules to approach the basal membrane. reversibly with K ATP channels (61), and both syntaxin and SNAP-25 also bind to L-type voltage-gated Ca 2ϩ channels (60,145). This is reminiscent of vascular smooth muscle cells, in which integrin engagement can stimulate L-type Ca 2ϩ channels via FAK (151).…”
Section: Letting the Skeleton Out Of The Closetmentioning
confidence: 97%
“…MLCK (myosin light chain kinase) phosphorylates myosin IIA (event 8), which induces its relocalization and association with the actin ring surrounding granules [important for maintenance of the fusion pore in an open conformation and for providing energy for discharge of granule contents (event 9) as well as cortical actin remodeling (event 10)] to allow insulin granules to approach the basal membrane. reversibly with K ATP channels (61), and both syntaxin and SNAP-25 also bind to L-type voltage-gated Ca 2ϩ channels (60,145). This is reminiscent of vascular smooth muscle cells, in which integrin engagement can stimulate L-type Ca 2ϩ channels via FAK (151).…”
Section: Letting the Skeleton Out Of The Closetmentioning
confidence: 97%
“…NBF1 has previously been shown to play a role in binding EPAC2 (37) and syntaxin-1A (38,39). IP studies revealed that STIM1 and FLAG-NBF1 co-immunoprecipitated, suggesting that NBF1 forms at least one interaction site between STIM1 and SUR1 proteins (Fig.…”
Section: Stim1 Activates K Atp and Soc Channels In ␤-Cellsmentioning
confidence: 99%
“…An increase in [Ca 2ϩ ] ER will induce translocation of STIM1 away from the plasma membrane to inactivate SOCE. A second possibility is that the rise in intracellular ATP will cause displacement of STIM1 from binding to SUR1, analogous to the effects of ATP on syntaxin binding (39). Displacement of STIM1 from SUR1 by ATP would contribute to the inhibition of K ATP channels after a rise in blood glucose.…”
Section: Stim1 Activates K Atp and Soc Channels In ␤-Cellsmentioning
confidence: 99%
“…First, syntaxin 1A interacts with the NBD1 of SUR subunits via its C-terminal H3 domain to decrease the activity of existing plasma membrane K ATP channels when ATP levels are lowered [58][59][60] . This effect is subject to ATP regulation, such that ATP dose-dependently inhibits syntaxin 1A binding to SUR1 subunits at physiological concentrations [61] . Second, it causes downregulation of K ATP channel expression, either by accelerating endocytosis of existing surface channels, or by decreasing the biogenesis of K ATP channels in the early secretory pathway [62] .…”
Section: Wwwchinapharcom Quan Y Et Almentioning
confidence: 99%
“…Since diazoxide is not very effective for CHI patients with K ATP channel mutations, alternative approaches for treating these patients may be to examine novel regulators of K ATP channels. One such molecule is syntaxin 1A, which inhibits K ATP channels [61] . Therefore, decreases in syntaxin 1A levels can increase K ATP channel activity.…”
Section: Congenital Hyperinsulinismmentioning
confidence: 99%